Multiplicação de Diaphorina citri e de Candidatus Liberibacter asiaticus em híbridos de citros indicados como porta-enxerto - Baia, Ana Dulce Botelho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Huanglongbing (HLB), or greening, is a disease that in Brazil is associated to the Candidatus Liberibacter asiaticus and Ca. Liberibacter americanus, both transmitted by the insect Diaphorina citri Kuwayama (Hemiptera: Liviidae). HLB is a disease highly destructive and of difficult control. Nowadays Ca. L. asiaticus ismost frequently found in citrus orchards. No commercial variety is resistant to the pathogen or insect vector. In order to satisfy grower necessity for more productive rootstocks and that promote smaller canopies to facilitate harvesting, several new hybrids have been tested for planting in the last years, For these hibrids no information exist on their potential in limiting the multiplication of the HLB bacteria or the vector, which could be used in disease management. In view of this, the objective of the present work was to evaluate multiplication rates of Ca. L. asiaticus and D. citri on five new hybrids suitable for use as rootstocks. For comparison purposes, the commercial rootstocks 'Cravo' Rangpur lime, 'Swingle' citrumelo, Poncirus trifoliata, and 'Sunki' mandarin, the sweet orange variety 'Valencia', and the ornamental orange jasmine Murraya exotica also were included in the study. D. citri multiplication was determined in healthy young shoots by daily counting of the number of eggs, nymphs and adults generated from two adult mating pairs, after confining them for 72 hours on the shoots or until eggs were observed. Ca. L. asiaticus multiplication was evaluated by quantitative PCR on the aerial part and roots of the plants, six months after stem graft inoculation. Influence of genotypes was observed on the multiplication of the insect as well as on the multiplication of the bacteria. The higher number of eggs was found on the hybrid 81G513 and on the orange 'Valencia', and the lower number of eggs on P. trifoliata. Nymph viability was higher on orange jasmine and P. trifoliata and lower on the ...

Huanglongbing (HLB) ou greening é uma doença que, no Brasil, está associada às bactérias Candidatus Liberibacter asiaticus e a Ca. L. americanus, ambas transmitidas pelo inseto Diaphorina citri Kuwayama (Hemiptera: Liviidae). O HLB uma doença altamente destrutiva e de difícil controle, sendo atualmente Ca. L. asiaticus a mais frequentemente encontrada nos pomares. Nenhuma variedade explorada comercialmente é resistente ao patógeno ou ao inseto vetor. Visando suprir as necessidades dos produtores por porta-enxertos mais produtivos e que promovam redução no volume da copa, diversos híbridos têm sido testados para uso comercial nos últimos anos. Sobre esses novos híbridos nada se sabe sobre seu potencial em limitar o desenvolvimento da bactéria do HLB ou do inseto vetor, características que poderiam ser úteis no manejo da doença. Em vista disso, o objetivo do presente trabalho foi avaliar taxas de multiplicação de Ca. L. asiaticus e de D. citri em cinco novos híbridos indicados para uso como porta-enxertos. Para fins de comparação foram também incluídos no estudo os porta-enxertos comerciais limoeiro 'Cravo', o citrumeleiro 'Swingle', Poncirus trifoliata, a tangerineira 'Sunki', variedade de laranja doce 'Valência', e a planta ornamental murta (Murraya exotica). A multiplicação de D. citri foi determinada em brotos jovens sadios pela contagem diária do número de ovos, ninfas e adultos gerados do acasalamento de dois casais confinados por 72 horas ou até que ovos fossem visualizados. A multiplicação de Ca. L. asiaticus foi avaliada por meio de PCR quantitativo em raízes e na parte aérea das plantas seis meses após a inoculação do caule por enxertia de ramos doentes, Influência dos genótipos foi detectada tanto na multiplicação do inseto como na multiplicação da bactéria. Maior número de ovos foi encontrado no híbrido 81G513 e na laranjeira 'Valência', e menor número em...
Keywords: Cítricos; Cítricos - Doenças e pragas; Porta-enxertos; Bacterias fitopatogenicas; Reação em cadeia de polimerase; Rootstocks